A Multi-Room Transition Dataset for Blind Estimation of Energy Decay - Götz, Philipp; Gotz, Georg; Meyer-Kahlen, Nils; Lee, Kyung Yun; Prawda, Karolina; Habets, Emanuël; Schlecht, Sebastian (2024 18th International Workshop on Acoustic Signal Enhancement (IWAENC), 2024)
We present an acoustic room impulse response dataset focusing on multi-room environments characterized by complex geometries and acoustic conditions. The dataset is accompanied by positional information and visual documentation in the form of 360° photographs. Additionally, we present a method to estimate acoustic energy decay functions from noisy, reverberant speech signals. We demonstrate the effectiveness of the proposed method based on experiments conducted with the presented dataset.
CRIS-Team Scopus Importer:2024-11-01
Keywords: dataset; energy decay functions; Multi-room acoustics